Delineations of culture - Holtbrügge, Dirk; Kirste, Laura (Elgar Encyclopedia of Cross-Cultural Management, 2024)
This entry describes various ways of delineating national culture, highlighting the advantages and disadvantages of five major approaches: legal-political, geographic, ethnic, linguistic, and intellectual-historical delineations. The legal-political approach, the most common, associates citizens with a specific culture, emphasising shared values and history. Geographic delineation involves residents, considering diasporas and regional sub-cultures, but modern means of communication weaken its relevance. Ethnic delineation focuses on shared ancestry and social constructs, while linguistic delineation assumes cultural similarities among speakers of the same language. Intellectual-historical delineation clusters cultural spheres based on shared worldviews, although it may oversimplify diverse values.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cultural differences; Delineations; Ethnic; Ethnicity; Geography; History; Legal; Linguistics; National culture; Nations; Political

Experiential Learning in the Digital Context: An Experimental Study of Online Cultural Intelligence Training - Kirste, Laura; Holtbrügge, Dirk (Journal of Teaching in International Business, 2019)
Digital transformation has opened novel opportunities for educators to approach the challenges of educating tomorrow's business leaders and managers. New methods of instruction such as blended learning and e-learning allow to cater better to a generation of digital natives and to enhance their learning ability. In the fast-moving business world, different cultures become increasingly intertwined which calls for managers who can function effectively in situations characterized by cultural difference. Hence, IB educators need to provide intercultural learning opportunity to a generation that lives on the intersection of the digital and analogue world. This paper presents and tests an approach to intercultural training by translating experiential teaming into a digital context. Drawing on the results, enhancements and future directions for IB scholars and educators are offered.
CRIS-Team WoS Importer:2019-10-15
Keywords: Kulturelle Vielfalt

Huawei at Bay? A View on Dependency Theory in the Information Age - Kirste, Laura; Holtbrügge, Dirk (Palgrave Studies of Internationalization in Emerging Markets, 2020)
Kirste and Holtbrügge analyze Huawei’s role in the global power play of establishing the 5G network rollout, adding to the scientific discussion of 5G on both a business and society level. This chapter takes an innovative approach by applying a theoretical framework to the recent debate on Huawei’s 5G participation and evaluating the prevalent perspectives on digitalization in China, the EU, and the USA. Building on dependency theory, dynamic power asymmetries of governments and multinational corporations in the Huawei case are analyzed and discussed. The authors find that the network structures of both multinational enterprises and 5G technology pose significant potential for countries to gain influence and power over other governments. Subsequently, theory-informed insights for practitioners and policymakers in the field of 5G are provided.<br
Keywords: 5G; Cyber-security; Dependency theory; Public policy; Power asymmetry

Intercultural training methods - Holtbrügge, Dirk; Kirste, Laura (Elgar Encyclopedia of Cross-Cultural Management, 2024)
This entry provides a typology of intercultural training methods differentiating between culture-specific and culture-general training, as well as experiential and intellectual. It discusses the various methods of instruction and technologies that enhance the accessibility and reach of intercultural training. Various considerations for increasing the effectiveness of intercultural training are outlined.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cross-cultural; Education; Experiential training; Intellectual training; Intercultural training; Online training; Training

Intracultural diversity - Holtbrügge, Dirk; Kirste, Laura (Elgar Encyclopedia of Cross-Cultural Management, 2024)
This entry highlights nuances of intracultural diversity, emphasising that within-country variations can surpass intercultural differences. It distinguishes three conceptual foundations: level-based, variance-based, and pattern-based. Level-based concepts attribute cultural differences to regional, state, or district variations within a country, employing frameworks such as Hofstede's dimensions. Variance-based concepts, such as Gelfand's tightness–looseness and ethno-linguistic fractionalisation, measure cultural diversity by accounting for within-country variations. Pattern-based concepts, exemplified by cultural archetypes, explore the combined configuration of cultural dimensions. It suggests managerial considerations, such as the impact of intracultural diversity on expatriates and its relevance in foreign acquisitions.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cultural differences; Diversity; Emic; Etic; Level-based; Pattern-based; Variance-based; Within-country differences

What drives the dissemination of CSR practices in global value chains? An institutional and psychological perspective - Kirste, Laura; Oberhauser, Marc; Holtbrügge, Dirk (International Business Review, 2023)
This study investigates how supply chain professionals in buying and supplying firms are motivated to engage in corporate social responsibility (CSR) practices within global value chains (GVCs). Based on the multiple needs theory of justice, social exchange theory, and the institution-based view, we develop hypotheses and test them against data collected from 201 supply chain professionals. We find that buyers’ intentions to cascade CSR practices to suppliers is particularly driven by instrumental and relational motives. In contrast, suppliers’ intentions to engage in CSR is largely determined by moral outrage. Moreover, significant effects are revealed for the institutional conditions on buyers’ CSR cascading intentions and on suppliers’ CSR implementation intentions. The misalignment between buyers’ and suppliers’ motives to engage in CSR activities is discussed as a major challenge of cascading CSR practices in GVCs. The study contributes to the international business literature by combining an institutional and psychological examination of individuals’ motivation to engage in CSR along GVCs. Moreover, we derive practical implications for supply chain managers.
CRIS-Team Scopus Importer:2023-11-10
Keywords: CSR; Global value chains; Institutional theory; Multiple needs theory of justice; Social exchange theory; Kulturelle Vielfalt